Edukasi robotika untuk mingkatkan kemampuan motorik halus di SD Baiturrahman - Irfan Darmawan; Warih Puspitasari; R. Wahjoe Witjaksono; Rohmat Gunawan; Alam Rahmatulloh (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2023)
Current formal education does not only focus on developing scientific and theoretical knowledge, but also pays attention to thought processes and behavior. Extracurricular activities are a means that can be optimized to improve thinking skills or behavior. Of the various kinds of extracurricular activities that exist, robotics is one of the new extracurricular activities, but is very much liked by students. Limited human resources who understand robotics and school support is one of the challenges in introducing robotics technology, especially for elementary school (SD) students. The solution to addressing this problem is that in this community service activity socialization and workshops on assembling robots for elementary school students are carried out. There are three main stages carried out in service activities: initial preparation, implementation, evaluation and reporting. Activities during the implementation of activities, begins with the introduction of robot components to be assembled. Participants in the activity totaling 37 students were divided into 6 groups. Each group was guided to follow the steps of assembling the robot, which consisted of: assembling several robot components and tightening the screws using a screwdriver, uploading the previously made computer program to the chip installed on the robot, activating the robot and controlling it via a smartphone. Partners filled out the questionnaire after the main activities were carried out. Partner responses to 6 statements related to the implementation of community service activities, on average giving a value in the category S = Agree, this means that partners agree and support this community service activity.